GREEN TECHNOLOGY FOR SUSTAINABLE AGRICULTURE: BIO-FERTILIZER PRODUCTION FROM MUNICIPAL WASTE TO PRESERVE THE ENVIRONMENT - Muhamad Afifi Muhamad Sidik; Abdul Mutalib Leman; Dafit Feriyanto; Samir Sani Abdulmalik; Supaat Zakaria (Universitas Mercu Buana, 2023)
This study addresses the pressing issue of municipal waste (MW) management by proposing an innovative approach to transform residential solid waste into a valuable resource using green technology. MW, sourced from diverse sectors, undergoes various disposal methods, including incineration, recycling, and landfilling. In Malaysia, the composition of MW aligns with global trends, with food waste and plastic being the predominant categories. This research focuses on producing fertilizer from residential solid waste through a green technology process, utilizing a sequential procedure involving high pressure, high temperature, and energized water to de-polymerize hemicellulose and lignin, followed by microbial enzymatic fermentation. The developed green technology introduces a novel apparatus designed for treating MW in a high-temperature, low-pressure rotating vessel using indirect heating with thermal fluid. The experimental protocol involves four batches of MW samples, evaluating the mass differential before and after the treatment process. Furthermore, a 7-week observation period assesses chili plant growth as an indicator of fertilizer effectiveness. Results indicate a significant 71% mass reduction of MW, amounting to 201.26 kg, emphasizing the efficacy of the developed process. The investigation extends to plant height, comparing MW-derived fertilizer with commercial fertilizer over a 5-week period. Remarkably, chili plants fertilized with MW-derived fertilizer exhibit a greater height of 8.6 cm, surpassing the 7.3 cm observed with commercial fertilizer. This study concludes that MW-derived fertilizer is highly recommended for enhancing plant growth and health in Malaysia, suggesting a sustainable production system. The research not only contributes to waste management but also aligns with broader goals of promoting environmentally conscious and sustainable agricultural practices, emphasizing the potential of green technology in addressing the challenges of municipal waste.